Exploring EFL Student-Teachers’ Metacognitive Awareness in Extensive Listening (Universitas Jambi, Magister Program of English Education Department, 2019)
Listening plays a vital role in the field of foreign and second language learning. The study aimed to explore which types of metacognitive awareness and how participants employed it when they practiced Extensive listening outside the classroom. The participants involved in the study were two undergraduate students in one of the state universities in Indonesia. Both of them are males majoring in English Department in teaching training faculty. The study used a Case study research design. Semi-structured interview and documentation were used as a tool to collect the data. The instrument was adapted and derived based on Metacognitive Awareness Listening theory of Vandergrift et al (2006). The study revealed that students used problem-solving strategy, person Knowledge, and mental translation. The study implies that students should raise awareness in the listening process by knowing about themselves, listening Task and strategies they use to help their listening development. Besides that, teachers need to use metacognitive instruction to increase students’ metacognitive listening awareness.